1997
DOI: 10.1159/000201484
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Z-103 on TNB-lnduced Colitis in Rats

Abstract: Z-103 is a chelate compound consisting of zinc ion and .L-carnosine. In this study, we investigated the protective effect of Z-103 against colonic damage induced by 2,4,6-trinitrobenzene sulfonic acid (TNB) in rats. Colonic inflammation was induced by administering TNB dissolved in 50% ethanol (120 mg/ml) in male Wistar rats (total volume of 0.25 ml per rat) following a 48-hour fast. After the administration of TNB, Z-103 was given at a dose of 30 mg/kg per rat for 1 week. A second group of rats received sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 14 publications
1
38
0
Order By: Relevance
“…Two lines of evidence support our hypothesis: (1) lipid peroxides significantly accumulate in the gastrointestinal mucosa during development of mucosal injury or inflammation, and (2) pretreatment with superoxide dismutase (SOD, a superoxide scavenger) or a hydroxyl radical scavenger greatly attenuates these injuries, as well as inhibiting the increase in lipid peroxides. It has also been proposed that oxygen radical-mediated lipid peroxidation is involved in the development of tissue injury in Crohn's disease and ulcerative colitis [8][9][10], as well as experimental colitis in animal models [4]. Several animal models of human inflammatory bowel disease have been studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two lines of evidence support our hypothesis: (1) lipid peroxides significantly accumulate in the gastrointestinal mucosa during development of mucosal injury or inflammation, and (2) pretreatment with superoxide dismutase (SOD, a superoxide scavenger) or a hydroxyl radical scavenger greatly attenuates these injuries, as well as inhibiting the increase in lipid peroxides. It has also been proposed that oxygen radical-mediated lipid peroxidation is involved in the development of tissue injury in Crohn's disease and ulcerative colitis [8][9][10], as well as experimental colitis in animal models [4]. Several animal models of human inflammatory bowel disease have been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Tamai et al [12] have reported a new model of colitis in rats in which the colon level of lipid peroxides was significantly increased by administration of 2,2'-azobis(2-amidinopropane)dihydrochloride (AAPH). We have also shown in a model of TNBS-induced colitis that lipid peroxides are increased significantly in the colonic mucosa [4], and treatment with SOD improves the colitis score [13]. Several studies on human inflammatory bowel disease confirm that oxidative stress is created by overproduction of reactive oxygen species or by the decrease in plasma concentrations of antioxidants, including vitamins C and E [9,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc supplementation has been reported to decrease the severity of radiation-induced mucositis in patients with head and neck cancer (12,13). In addition, PZ, which is a chelate compound consisting of a zinc ion, L-carnosine, a β-alanine dipeptide and L-histidine, has been reported to be more effective in terms of superoxide scavenging activity compared to zinc sulfate (5). Therefore, the efficacy of PZ for radiation-induced mucositis appears to be promising.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PZ has antioxidant properties and scavenges free radicals (4)(5)(6)(7). We previously reported the efficacy of PZ for acute radiation proctitis in an animal model and demonstrated that PZ exerts anti-inflammatory effects following radiation exposure (8).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high dose of zinc has been shown to improve tight-junction permeability (209). A novel zinc compound, Z-103, a chelate compound consisting of zinc ion and L-carnosine, was utilized to assess the protective effect against colonic damage www.intechopen.com induced by TNBS in rats (210). The authors demonstrated that treatment with Z-103 reduced he inflammatory responses induced by TNBS, suggesting Z-103 may be as effective against TNBS-induced colitis.…”
Section: Animal Studiesmentioning
confidence: 99%